Improving patient outcomes : The pivotal role of guideline directed medical treatment - Hasanah, Dian Yaniarti (Heart Science Journal, 2026)
Guideline directed medical therapy (GDMT) continues as the main pillar of management for heart failure with reduced ejection fraction (HFrEF). Numerous positive landmark trials and emergence of novel drugs provide strong evidence supporting the capability of GDMT in reducing cardiovascular mortality, hospitalization due to heart failure (HHF), and advancement of renal impairment. The introduction of a four-pill regimen comprising five specific pharmacological agents represents a major shift in disease-modifying care, significantly slowing symptomatic decline and improving long-term survival outcomes. Despite strong clinical recommendation, there is a huge gaps in the implementation of clinically-proven pharmacological strategies for eligible patients that further linked to relatively persistently flat mortality curves of HfrEF patients. Effective adherence to HF guidelines is often hindered by a multifaceted interplay of patient-related hurdles, clinical inertia, and systemic healthcare limitations. These challenges are further compounded by age-related complexities and multimorbidity, where concerns over pill burden and inadequate disease literacy frequently lead to suboptimal therapeutic outcomes.